First-order thermodynamics of Horndeski cosmology - Miranda, Marcello; Giardino, Serena; Giusti, Andrea; Heisenberg, Lavinia (Physical review, 2024)
We delve into the first-order thermodynamics of Horndeski gravity, focusing on spatially flat, homogeneous, and isotropic cosmologies. Our exploration begins with a comprehensive review of the effective fluid representation within viable Horndeski gravity. Notably, we uncover a surprising alignment between the constitutive relations governing the “Horndeski fluid” and those of Eckart’s thermodynamics. Narrowing our focus, we specialize our discussion to spatially flat Friedmann-Lemaître-Robertson-Walker spacetimes. Within this specific cosmological framework, we systematically analyze two classes of theories: shift symmetric and asymptotically shift symmetric. These theories are characterized by a nonvanishing braiding parameter, adding a nuanced dimension to our investigation. On the one hand, unlike the case of the “traditional” scalar-tensor gravity, these peculiar subclasses of viable Horndeski gravity never relax to General Relativity (seen within this formalism as an equilibrium state at zero temperature), but give rise to additional equilibrium states with nonvanishing viscosity. On the other hand, this analysis further confirms previous findings according to which curvature singularities are “hot” and exhibit a diverging temperature, which suggests that deviations of scalar-tensor theories from General Relativity become extreme at spacetime singularities. Furthermore, we provide a novel exact cosmological solution for an asymptotically shift-symmetric theory as a toy model for our thermodynamic analysis.